2014
DOI: 10.1016/j.neuron.2014.10.046
|View full text |Cite
|
Sign up to set email alerts
|

CaMKI-Dependent Regulation of Sensory Gene Expression Mediates Experience-Dependent Plasticity in the Operating Range of a Thermosensory Neuron

Abstract: SUMMARY Sensory adaptation represents a form of experience-dependent plasticity that allows neurons to retain high sensitivity over a broad dynamic range. The mechanisms by which sensory neuron responses are altered on different timescales during adaptation are unclear. The threshold for temperature-evoked activity in the AFD thermosensory neurons (T*AFD) in C. elegans is set by the cultivation temperature (Tc), and regulated by intracellular cGMP levels. We find that T*AFD adapts on both short and long timesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
134
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(150 citation statements)
references
References 35 publications
(66 reference statements)
14
134
2
Order By: Relevance
“…Elevated Ca 2ϩ modulates thermotaxis by upregulating Ca 2ϩ /calmodulin-activated protein kinase 1 (CMK-1) or calcineurin (TAX-6), a protein phosphatase. CMK-1 induces gcy gene expression, whereas TAX-6 is required to sustain optimal TAX-2/TAX-4-mediated Ca 2ϩ uptake (59,60). Neither CMK-1 nor TAX-6 directly regulates NT or NP release from vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated Ca 2ϩ modulates thermotaxis by upregulating Ca 2ϩ /calmodulin-activated protein kinase 1 (CMK-1) or calcineurin (TAX-6), a protein phosphatase. CMK-1 induces gcy gene expression, whereas TAX-6 is required to sustain optimal TAX-2/TAX-4-mediated Ca 2ϩ uptake (59,60). Neither CMK-1 nor TAX-6 directly regulates NT or NP release from vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral acclimation to T c is reflected in part by adaptation of the thermosensory response threshold ( T* AFD ) of the bilateral AFD sensory neuron pair (Biron et al, 2006; Clark et al, 2006; Kimura et al, 2004; Mori and Ohshima, 1995; Ramot et al, 2008; Yu et al, 2014). Measurements of intracellular calcium dynamics and temperature-evoked currents have shown that AFD depolarizes and hyperpolarizes upon warming and cooling, respectively, at temperatures warmer than T* AFD to drive thermotaxis behaviors (Clark et al, 2006; Kimura et al, 2004; Ramot et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On December 3, 2014, two research articles [59,60] were published in Neuron on the subject of C. elegans ’ ability to alter thermotaxis based on past experience. These studies built on years of work showing that CaM Kinase cascade signals to CREB and other transcription factors in the nematode [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…Nematodes adapted their thermotaxis behavior, tolerating warmer temperatures if they had been incubated at higher temperatures. CMK-1 regulates this physiological set point via modulation of guanylyl cyclase gene ( gcy ) expression levels [60]. In FLP nociceptors, cytoplasmic CMK-1 promotes thermal avoidance in the face of noxious temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation